PHYSICAL SELF-CONCEPT OF MEXICAN ATHLETE AND NON-ATHLETE TEENAGERS - Zueck, Maria Del Carmen; Gastelum, Gabriel; Munoz, Francisco; Benavides, Veronica; Peinado, Jesus Enrique (European Scientific Journal, ESJ, 2015)
The purpose of this study consists of outlining the differences and similarities between elementary and junior-high school Mexican students’ physical self-concept based on the variables of those who practice a sport on a regular basis and those who do not do. A total sample of 596 male students, between the ages of 11-16 participated in this study; 270 of them practice a sport and participate regularly in tournaments or competitions. A quantitative approach with a descriptive and transversal survey design was used. All the participants completed the Physical Self-Description Questionnaire. The results of the one-way multivariate analysis of variance, followed by the oneway univariate analyses of variance, show that students who do not participate in sports regularly are the ones who obtained lower scores on the coordination, activity, sports competence, appearance, strength, flexibility, endurance, global physical self-concept, and global self-esteem subscales. However, in the health subscale, statistically significant differences were not found. Further research should seek these findings in larger samples.